Artificial Intelligence: A salvation for students or an obstacle on the way to knowledge? (MMIT Proceedings, 2024)
Academic fields are increasingly adopting artificial intelligence (AI) technologies to improve the learning process. However, questions arise about how effective the use of AI in education is and whether it can lead to improvements or, conversely, hinder students' knowledge acquisition. The article analyzes various aspects of the impact of AI on the educational process, including automation of assessment, personalization of learning, reducing the risk of errors, and many others. It examines both the positive and potentially negative aspects of introducing AI into education, and also suggests possible strategies for optimizing the use of AI technologies in the educational process.